Impact of a multidisciplinary team “ECMO Team” on the prognosis of patients undergoing veno-arterial extracorporeal membrane oxygenation for refractory cardiogenic shock and cardiac arrest - Seoane, Leonardo A. (2023)
Objectives. Veno-arterial Extracorporeal membrane oxygenation (VA ECMO) is a salvage intervention in patients with cardiogenic shock (CS), and cardiac arrest  (CA) refractory to standard therapies. The design of ECMO Teams has achieved the standardization of processes, although its impact on survival and prognosis is unknown. Objective: We aimed to analyze whether the creation of an ECMO Team has modified the prognosis of patients undergoing VA ECMO for refractory CS or CA. Materials and methods. We conducted a single-center retrospective cohort study. Patients with refractory CS or CA who underwent VA ECMO were divided in two consecutive periods: from 2014 to April 2019 (pre-ECMO T) and from May 2019 to December 2022 (Post ECMO T). The main outcomes were survival on ECMO, in-hospital survival, complications, and annual ECMO volume. Results. Eighty-three patients were included (36 pre-ECMO T and 47 post-ECMO T). The mean age was 53 +/-13 years. The most common reason for  device indication was different:  postcardiotomy shock (47.2%) pre-ECMO T and refractory cardiogenic shock (29.7%) post-ECMO T. The rate of extracorporeal  cardiopulmonary resuscitation was 14.5%.  The median duration of VA ECMO was longer after ECMO team implementation: 8 days (IQR 5-12.5) vs. five days (IQR 2-9, p=0.04). Global in-hospital survival was 45.8% (38.9% pre-ECMO T vs. 51.1% post-ECMO T; p=0.37),  and the survival rate from VA ECMO was 60.2% (55.6% pre-ECMO T vs 63.8% post-ECMO T; p= 0.50). The volume of VA ECMO implantation was significantly higher in the post-ECMO team period (13.2  +/3.5 per year vs. 6.5 +/-3.5 per year, p: 0.02). The rate of complications was similar in both groups. Conclusions. After the implementation of an ECMO team, there was no statistical difference in the survival rate of patients treated with VA ECMO. However, a significant increase in the number of patients supported per year was observed after the implementation of this multidisciplinary team. Post-ECMO T, the most common reason for device indication was cardiogenic shock, with longer run times and a higher rate of extracorporeal cardiopulmonary resuscitation.